Pertumbuhan Dan Hasil Tanaman Padi Varietas Inpari 23 Pada Tiga Jenis Tanah Yang Mendapat Pembenah Tanah dengan Berbasis Pupuk Organik Bio-Slurry - Puguh Jati Nugroho; Sumarsono Sumarsono; Sutarno Sutarno (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
AbstractThe study was conducted to the effect of soil amendment on the growth and production of three Inpari 23 rice plants on three types of soil. The research design used was a split-plot experiment, with 3 replications. The main plot of soil from the location consisted of andosol soil type from Karanganyar (L1), Mediterranean soil type from Magelang (L2), and alluvial soil type from Demak (L3). Sub-plots are without soil amendment (R1) and with soil amendment (R2). Parameters observed were plant height, number of tillers, the weight of plant crown, and harvest index. The data obtained were statistically analyzed by analysis of variance prosedure, and the LSD test at the 5% level for to comparation the difference mean between treatments. The results showed that the interaction effect between the treatment of soil improvement and the type of soil from three locations was significant (P<0,05) based on the parameters of the number of tillers and the weight of the plant crown. The conclution of the study that the growth and production of the Inpari 23 variety were highest with soil improvement (R2 on the alluvial soil type from Demak (L3), followed by the Mediterranean soil type from Magelang. (L2) and of the andosol soil type from Karanganyar (L3). Keywords: Growth; Paddy; Soil Repairer; Organic fertilizer.